Early oral feeding following intestinal anastomosis surgery in infants: a multicenter real world study - Lu, Changgui; Sun, Xinhe; Geng, Qiming; Tang, Weibing (Frontiers in Nutrition, 2023)
Background To prevent postoperative complications, delayed oral feeding (DOF) remains a common model of care following pediatric intestinal anastomosis surgery; however, early oral feeding (EOF) has been shown to be safe and effective in reducing the incidence of complications and fast recovery after pediatric surgery. Unfortunately, the evidence in support of EOF after intestinal anastomosis (IA) in infants is insufficient. Therefore, this study was primarily designed to evaluate the safety and efficacy of EOF. In addition, the current status of EOF application and associated factors that favor or deter EOF implementation were also assessed. Methods A total of 898 infants were divided into two groups (EOF group, n=182; DOF group, n=716), and the clinical characteristics were collected to identify the factors associated with EOF in infants. Complications and recovery were also compared to define the safety and efficacy after balancing the baseline data by propensity score matching (PSM) (EOF group, n=179; DOF group, n=319). Results The total EOF rate in infants with IA was 20.3%. Multivariate logistic regression revealed significant differences in the EOF rates based on IA site and weight at the time of surgery (OR = 0.652, 95% CI: 0.542−0.784, p<0.001) and (OR ＝ 1.188, 95% CI: 1.036−1.362, p=0.013), respectively. The duration of total parenteral nutrition (TPN), parenteral nutrition (PN), and postoperative hospital stay were significantly shorter in the EOF group than the DOF group[2.0 (1.0,2.0) d vs. 5.0 (3.0,6.0) d; 6.0 (5.0,8.0) d vs. 8.0 (6.0,11.0) d; 10.0 (7.0,14.0) d vs. 12.0 (9.0,15.0) d, all p<0.001]. The rates of abdominal distension and vomiting in the EOF group were significantly higher than the DOF group (17.9% vs. 7.2%, p<0.001; 7.8% vs. 2.5%, p=0.006); however, no differences were found in failure to initial OF, diarrhea, hematochezia, and anastomotic leakage between the two groups (p>0.05). Conclusions The overall rate of EOF in infants following IA was low, and the sites of anastomosis and weight at surgery were two factors associated with EOF. Nevertheless, performing EOF in infants after IA was safe and effective, reduced PN usage, shortened the hospital stay, and did not increase the rate of severe complications.